Polyaxial pedicle screw external fixation to stabilize oblique mandibular fractures in three standing, sedated horses. Issue 3 (19th February 2021) - Nelson, Brad B.; Easley, Jack; Steward, Sara K. T.; Smanik, Lauren E.; Koch, Drew W.; Rawlinson, Jennifer E.; Easley, Jeremiah T.
Abstract: Objective: To report the radiographic, surgical and postoperative features in horses with unstable oblique mandibular fractures secured with polyaxial pedicle screws (PPS) external fixation construct and intraoral wiring. Animals: Three client‐owned horses. Study design: Short case series. Methods: Two horses each had a unilateral fracture, which did not improve after conservative management, and one horse had bilateral fractures. Clinical and radiographic features were documented. Polyaxial pedicle screw external fixators and intraoral tension band wiring were applied in standing horses after combining sedation and regional nerve anesthesia. Intraoral wires were implanted through a lateral buccotomy between teeth (two horses) or burred through exposed crown (one horse) and then secured around the incisors. The PPS were inserted under radiographic guidance to avoid tooth roots. Healing was assessed with radiographic examination. The PPS external fixator rod and intraoral wires were removed first. The mandible was manipulated, and, if it was stable, the PPS were removed. Results: Implants were removed at 6, 8, or 10 weeks after the mandibles were palpably stable. Complications included broken wires in one horse, bone sequestration in one horse, and infection in one horse. Follow‐up communication with the owners 12 to 18 months later confirmed complete healing without further complications of the fractured mandibles or teeth. Conclusion: Polyaxial pedicle screw external fixation led to fracture healing and a return to function in all three horses. The complications encountered did not preclude a successful outcome. Clinical significance: Polyaxial pedicle screw external fixation coupled with intraoral wiring provides an alternative to treat unstable equine mandibular fractures without general anesthesia.